2018
DOI: 10.7771/1932-6246.1200
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Goal in Solving Hard Computational Problems: Do People Really Optimize?

Abstract: The role that the mental, or internal, representation plays when people are solving hard computational problems has largely been overlooked to date, despite the reality that this internal representation drives problem solving. In this work we investigate how performance on versions of two hard computational problems differs based on what internal representations can be generated. Our findings suggest that problem solving performance depends not only on the objective difficulty of the problem, and of course the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 30 publications
(45 reference statements)
1
8
0
1
Order By: Relevance
“…It also established that participants were able to reliably detect diff erences in areas of these magnitudes, thereby confi rming that area diff erences could provide a feasible heuristic for making length comparisons. Carruthers (2015) proposed that when problem solvers are faced with a problem where it is infeasible to identify whether or not the goal has been reached, they may modify the goal into one that is feasible to identify. In the case of the E-TSP, an example of a possible modifi ed goal is "a valid tour" (p. 49).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It also established that participants were able to reliably detect diff erences in areas of these magnitudes, thereby confi rming that area diff erences could provide a feasible heuristic for making length comparisons. Carruthers (2015) proposed that when problem solvers are faced with a problem where it is infeasible to identify whether or not the goal has been reached, they may modify the goal into one that is feasible to identify. In the case of the E-TSP, an example of a possible modifi ed goal is "a valid tour" (p. 49).…”
Section: Discussionmentioning
confidence: 99%
“…In the psychology of problem solving and decision making, a longstanding answer to similar questions has been that problem solvers use heuristic procedures (Gigerenzer & Goldstein, 1996;Kahneman & Tversky, 1972;Simon, 1983;Tversky & Kahneman, 1973). However, before assuming that heuristics explain performance, Carruthers (2015) proposes that identifying the problem as encoded is important, "because the encoded problem drives performance" (p. 47). The present article explores this proposal by designing a task that meets the definition of having an indeterminable goal and showing that people, first, act as if they believe they can achieve the goal and, second, appear to use heuristics in trying to do so.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…By easier we mean faster, smaller error measure, or more effective with respect to cognitive/computational resources such as memory. Carruthers (2015) recently showed, using two examples, that humans can reformulate problems and work on the reformulated problem when the original problem exceeds their cognitive resources. Similarly, one of us has shown that when subjects are presented with a 15-tile puzzle, they move around one or at most two tiles at a time, putting them in the correct location and treating the remaining tiles that are still out of place as equivalent (Pizlo & Li, 2005).…”
Section: Introductionmentioning
confidence: 99%